2020
DOI: 10.1186/s12909-020-02142-0
|View full text |Cite
|
Sign up to set email alerts
|

Peer-teaching at the University of Rwanda - a qualitative study based on self-determination theory

Abstract: Background: Peer-teaching is an educational format in which one student teaches one, or more, fellow students. Self-determination theory suggests that intrinsic motivation increases with the enhancement of autonomy, competence and relatedness. Aims: This qualitative study sought to explore and better understand the lived experiences, attitudes and perceptions of medical students as peer-teachers at the University of Rwanda when participating in a peer-learning intervention in the pediatric department. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…Peer-teaching strategy 5 Students are in charge of the lessons under the teacher's supervision Low-performing students impacted positively Active teaching 6 Actively involves the students Enhances skill proficiency in the process as the students are not passively but actively involved Lecture strategy 7 Verbal relay of information Passive as compared to the active teaching strategy…”
Section: Strategy Definition Effectmentioning
confidence: 99%
“…Peer-teaching strategy 5 Students are in charge of the lessons under the teacher's supervision Low-performing students impacted positively Active teaching 6 Actively involves the students Enhances skill proficiency in the process as the students are not passively but actively involved Lecture strategy 7 Verbal relay of information Passive as compared to the active teaching strategy…”
Section: Strategy Definition Effectmentioning
confidence: 99%
“…They mostly participated in track and field events. The third group, on the other hand, was only involved in taekwondo [ 5 ]. The final group was the positive control involved in both sporting games and taekwondo activities.…”
Section: Methodsmentioning
confidence: 99%
“…It may be because of the fact that the tutors were one year senior to the learners but even same level peers had been shown to develop competency skills. 20 Studies on peer assisted tutoring has been documented to develop the skills, attitudes and practices of a competent teacher, 20,21 though no studies are found to see the long-term effect of such interventions on tutors.…”
Section: Subtheme B: Easy and Productive Transfer Of Knowledgementioning
confidence: 99%